Investigation of the cytokine status in patients during the acute period of intracranial arterial aneurysm rupture - Globa, Marina; Lisianyi, Nikolay; Tsimeyko, Orest; Belska, Lyudmila (Ukrainian Neurosurgical Journal, 2014)
Objective: Analyze the changes of -1β, -4, -6 interleukin indices in blood serum of patients during the acute period of intracranial arterial aneurysm (AA) rupture. Materials and methods: Levels of -1β, -4, -6 interleukins in the serum were analyzed in 37 patients during the acute period of intracranial arterial aneurysm (AA) rupture with the help of immune-enzyme analysis: in 27 patients on the 1–4th day since the manifestation of the disease; in 22 patients — on the 7–10th day after the haemorrhage (in 10 — recurrent). Clinical and instrumental examination of all the patients included brain CCT, cerebral angiography, ultrasonography; microsurgical exclusion of aneurysm was carried out according to indications. Results: The interleukin indices in the serum of patients with SAH were higher than those in the control group mainly on the 7–10th day after the SAH episode.The interleukin-6 level was 20–30 times higher compared to the average index of the control group. There was a reliable increase of its level in patients with cerebral vasospasm (VS) compared to those without VS (p<0,05). The interleukins-1β and -4 indices were moderately (2–5 times) increased in comparison with those in the control group, they did not differ significantly in patients with VS and without it. In patients likely to have grave incapacitation or fatal outcome interleukin-6 levels were significantly higher both during the first 4 days of the disease (p<0,05), and on the 7–10th day. Conclusions: The increased levels of -1β, -4 та -6 interleukins during the first 10 days after AA rupture indicate that there exist active inflammatory processes in this period of the disease, which gives grounds for the use of antiinflammatory therapy. A connection established between the increase of interleukin-6 level, presence of cerebral VS, as well as severity of the disease may be evidence of this cytokine’s significance in SAH.